Entre management et leadership : le « pilote » comme figure emblématique de l’activité des chefs d’établissement - Christiane Montandon; Marie Brégeon (Éducation et Socialisation)
The headteacher, representative of the school institution with a plurality of actors, appears as the nerve center and strategy of the implementation of the educational policy. The complexity of his missions lies in paradoxical injunctions: reconciling institutional autonomy and performance requirements in contexts that alternate and combine local, territorial and national issues. The field corpus is made of 12 interviews with heads of colleges, general and technological high schools, vocational high schools; the article analyzes how heads of establishments and directors of "Section d’enseignement général et professionnel adapté" (SEGPA) apprehend their role as leaders in the way of energizing and regulating the interactions between the various actors of the educational community by relying on the group mediations that are "Conseils d’administration" (CA), pedagogical, disciplinary councils, consultation commissions. The fundamental characteristics of the concept of leadership in social psychology and the role of the socio-professional representations of the various members of the establishment make it possible to understand the way in which a headteacher can assume the double administrative and pedagogical dimension of this supervisory function. This analysis encourages us to privilege the role of leader instead of that of manager, which refers to an overly technicist conception, to underline the ethical and political dimensions which underlie the figure of the "pilot", guarantor of a just order respecting values expected of both teachers and students.